Investigating the Role of Extracellular Polysaccharides in Biofilm Formation of Klebsiella pneumoniae - MOYNIHAN, SINEAD (Trinity College Dublin. School of Medicine. Discipline of Clinical Microbiology, 2020)
Klebsiella pneumoniae (K. pneumoniae) is the most significant and clinically relevant species in the Klebsiella genus of Enterobacteriaceae and is the causative agent of a variety of infections, including pneumonia, urinary tract infections and bacteraemia. The success of K. pneumoniae in establishing infection in a variety of sites in a host is enhanced by the production of a wide range of virulence factors. Biofilm formation is an important factor in the lifestyle of K. pneumoniae. Conflicting data exist surrounding the relationship between the capsule polysaccharide (CPS) of Klebsiella and biofilm formation. Certain studies have found that mutations disrupting capsule synthesis result in biofilm reduction; whereas increased biofilm production has been observed as a result of capsule reduction. The composition of growth media is also considered a major determinant of biofilm formation. However, similar to the capsule, clarity is lacking surrounding the contribution of growth media to biofilm formation; nutrient-rich media has been shown to both hinder and enhance biofilm formation. This study sought to investigate the contribution of both capsule and growth media to the biofilm formation of K. pneumoniae strain Kp52145. Crystal violet assays were utilised to quantify biofilm formation. A capsule mutant lacking manC, a gene from the CPS operon of Kp52145, was utilised to investigate the role of capsule in biofilm formation and to establish whether the contribution of growth media was strain-characteristic-dependent. Alternative Klebsiella isolates were subsequently incorporated into biofilm studies in an attempt to decipher whether the observed effects of growth media on biofilm formation were more widely observed in the species. Additionally, capsular genotyping of these isolates was performed to determine whether capsular type of K. pneumoniae influences biofilm formation. In order to further decipher the role of capsule in biofilm formation, this study aimed to construct a Kp52145 CPS operon mutant, using Lambda-Red recombination technology. PCR-mediated gene replacement and a DNA assembly tool based on the Gibson Assembly technique were both utilised, however, transformation attempts were unsuccessful. The use of a bioluminescence system was evaluated as an alternative measurement of viability in biofilm formation assays but was deemed unfeasible due to intrinsic differences in bioluminescent signal among Kp52145 strains. Minimum Inhibitory Concentration (MIC) analysis of Kp52145 strains harbouring this plasmid-based bioluminescent system revealed differential antibiotic resistance to a particular beta-lactam/beta-lactamase inhibitor combination antibiotic. This study proposes that the anionic charge of the capsule contributes to this observed differential phenotype. Furthermore, this study aimed to investigate whether complementation of the Kp52145 manC mutant would restore the wild-type (WT) phenotype with regards to colony morphology, biofilm formation and antibiotic resistance. However, subsequent Polymerase Chain Reaction (PCR) analysis and Whole Genome Sequencing (WGS) revealed an intact manC gene and CPS operon. Instead, a deletion affecting a protein similar to a blue-light sensor in Escherichia coli (E. coli), YcgF, was identified. Therefore, results from this study were subsequently reinterpreted on the basis of this discovery.
APPROVED